Autotetraploid Emergence via Somatic Embryogenesis in Vitis vinifera Induces Marked Morphological Changes in Shoots, Mature Leaves, and Stomata - Caterina Catalano; Loredana Abbate; Antonio Motisi; Dalila Crucitti; Vincenzo Cangelosi; Antonino Pisciotta; Rosario Di Lorenzo; Francesco Carimi; Angela Carra (Cells, 2021)
Polyploidy plays an important role in plant adaptation to biotic and abiotic stresses. Alterations of the ploidy in grapevine plants regenerated via somatic embryogenesis (SE) may provide a source of genetic variability useful for the improvement of agronomic characteristics of crops. In the grapevine, the SE induction process may cause ploidy changes without alterations in DNA profile. In the present research, tetraploid plants were observed for 9.3% of ‘Frappato’ grapevine somatic embryos regenerated in medium supplemented with the growth regulators β-naphthoxyacetic acid (10 µM) and N6-benzylaminopurine (4.4 µM). Autotetraploid plants regenerated via SE without detectable changes in the DNA profiles were transferred in field conditions to analyze the effect of polyploidization. Different ploidy levels induced several anatomical and morphological changes of the shoots and mature leaves. Alterations have been also observed in stomata. The length and width of stomata of tetraploid leaves were 39.9 and 18.6% higher than diploids, respectively. The chloroplast number per guard cell pair was higher (5.2%) in tetraploid leaves. On the contrary, the stomatal index was markedly decreased (12%) in tetraploid leaves. The observed morphological alterations might be useful traits for breeding of grapevine varieties in a changing environment.